Emerging and Re-Emerging Diseases-Novel Challenges in Today's World - Mesquita, João R. (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
It is known today that more than 61% of human pathogens are zoonotic, representing 75% of all emerging pathogens during the past decade, presenting an increasing a matter of concern, particularly in modern days where global warming keeps is causing climatic conditions conducive to the introduction of exotic infectious agents or disease vectors in new territories. This book compiles studies that approach a myriad of zoonotic infectious diseases and their complex mechanisms. This is a brief but in-depth collection that showcases the need to address health at the animal-human-environment interface, in a One Health perspective.